A genome‐wide association study for equine recurrent airway obstruction in European Warmblood horses reveals a suggestive new quantitative trait locus on chromosome 13. (24th July 2017) - Schnider, D.; Rieder, S.; Leeb, T.; Gerber, V.; Neuditschko, M.
Summary: Recurrent airway obstruction (RAO), also known as heaves, is an asthma‐like respiratory disease. Its development is strongly influenced by environmental risk factors such as sensitization and exposure to moldy hay, straw bedding and stabling indoors. A hereditary component has been documented in previous studies; however, so far no causative genetic variant that influences the risk of developing RAO has been identified. In this study, we revised an existing dataset and selected 384 horses for genotyping on the Affymetrix high‐density equine SNP array. We performed an allelic case–control genome‐wide association study, which revealed a suggestively significant association on equine chromosome 13 at 32 843 309 bp. This SNP is located in the protein‐coding gene TXNDC11, which is possibly involved in the folding process of the multiprotein complexes DUOX1 and DUOX2. In humans, these proteins are known to take part in regulating the production of H2 O2 in the respiratory tract epithelium as well as in MUC5AC mucin expression. Therefore, TXNDC11 may be considered a functional candidate gene, and further research is needed to explore its potential role in RAO‐affected horses.